1963
DOI: 10.1051/lhb/1963055
|View full text |Cite
|
Sign up to set email alerts
|

A new method of predicting the flow in a 90° branch channel

Abstract: The discharge distribution decreases as the Froude number increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…It was observed that there is a strong linear relationship between the discharge ratio (Q r ) and the Froude number in all cases. Moreover, there is a reverse relationship between Q r and F u , which is consistent with the results of Krishnappa and Seetharamiah (1963), Hager (1987), and Bejestan et al (2013), and between Q r and F b . In addition, based on the maximum branch channel discharge, the best angle for the diversion channel is 45° from among 45, 60, 75, and 90°.…”
Section: Relationship Between Discharge Ratio and Froude Numbersupporting
confidence: 90%
“…It was observed that there is a strong linear relationship between the discharge ratio (Q r ) and the Froude number in all cases. Moreover, there is a reverse relationship between Q r and F u , which is consistent with the results of Krishnappa and Seetharamiah (1963), Hager (1987), and Bejestan et al (2013), and between Q r and F b . In addition, based on the maximum branch channel discharge, the best angle for the diversion channel is 45° from among 45, 60, 75, and 90°.…”
Section: Relationship Between Discharge Ratio and Froude Numbersupporting
confidence: 90%
“…Krishnappa and Seetharamiah (1963) and Ramamurthy and Satish (1988) used the inlet Froude number, which is not suitable (Fig. 5a), however.…”
Section: Empirical Correlation Of Discharge Distributionmentioning
confidence: 99%
“…This state is ensured if the Froude number in the lateral branch is larger than the threshold value of 0.34 (0.35 by Satish 1988 and1/3 by Hager 2010). The presence of a critical flow section was used to characterize the discharge division analytically (Ramamurthy and Satish 1988) or empirically (Krishnappa and Seetharamiah 1963, Lakshmana Rao and Sridharan 1967, Rivière et al 2007). This work focuses on different cases of transcritical flow division, namely junction inlet flow under the critical regime.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both empirical formulae (e.g. [9]) and simplified models based on macroscopic control volumes [10] have been derived for channel bifurcations, but in the case of a dike break, the flow leaving the main channel is not confined by lateral walls but can spread in all directions. There is therefore a need for a simplified model designed for the specific case of dike-break induced flows, all the more so because general empirical formulae (e.g.…”
mentioning
confidence: 99%